The cost of influence: How gifts to physicians shape prescriptions and drug costs - Melissa Newham; Marica Valente (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2023)
This paper studies how gifts - monetary or in-kind payments - from drug firms to physicians in the US affect prescriptions and drug costs. We estimate heterogeneous treatment effects by combining physician-level data on antidiabetic prescriptions and payments with causal inference and machine learning methods. We find that payments cause physicians to prescribe more brand drugs, resulting in a cost increase of 30 per dollar received. Responses differ widely across physicians, and are primarily explained by variation in patients' out-of-pocket costs. A gift ban is estimated to decrease drug costs by 3-4%. Taken together, these novel findings reveal how payments shape prescription choices and drive up costs.
Keywords: I11; I18; M31; 330; public health; payments to physicians; gift ban; heterogeneous treatment effects; causal machine learning